BIOTIC EVENTS AND POSITIVE δCCARB ANOMALY AT 2.3-2.06 GA - Semikhatov M.A.; Raaben M.E.; Sergeev V.N.; Veis A.F.; Artemova O.V. (My University, 1999)
A comprehensive analysis of taxonomic composition of pre-Riphean silicified and organic-walled microfossils described in publications is performed and dynamics of stromatolite abundance during the Archean and Paleoproterozoic is reconstructed based on a calculation of a number of stromatolite-bearing formations in seven time periods 300-400 m.y. long for the Archean and 200-300 m.y. long for the Paleoproterozoic. It is shown that the Jatulian positive δ13Ccarb anomaly, the largest one in the Earth's history that occurred 2.3-2.06 Ga ago was not related to evolutionary innovations in the ancient microbiota but was synchronous with the sharpest, in geological history, increase in the global stromatolite abundance. This event was controlled by a favorable combination of climatic, paleogeographic, and geodynamic factors and occurred under condition of the prevalence of the mantle flux into the World ocean over the continental runoff. Simultaneously, the transition to "normal marine" δ13Ccarb values that marked the termination of the Jatulian anomaly was accompanied by a slight increase in abundance of Paleoproterozoic stromatolites, which was reduced again only 1.8-1.6 Ga ago. It is concluded that the Jatulian anomaly was mainly related to the unique-scale expansion of cyanobacterial ecosystems that is recorded in stromatolite succession and occurred against the background of increasing oxygenation of atmosphere and surficial part of hydrosphere. Peculiarities of the C-isotope and paleontological records of the second half of the Paleoproterozoic are briefly discussed with consideration of probable factors responsible for the disappearance of the anomaly in question.
Keywords: Riphean; Archean; Paleoproterozoic; Докембрий::Протерозой::Рифей; Precambrian::Archean; Precambrian::Proterozoic::Paleoproterozoic; Precambrian::Proterozoic::Riphean; Докембрий::Архей; Докембрий::Протерозой::Палеопротерозойская